The Efficacy of Using Video Learning Media in Teaching English at Senior High School - Soleman Dapa Taka (Institut Agama Islam Negeri Palopo, 2024)
This study aimed to determine student perception after using English video learning media. The research method is a quantitative research method. The researcher uses pretest posttest control experiment to measure the effectiveness of Video Learning Media, before learning activity was held, the researcher determines students’ entry skill by giving them a pretest, furthermore the learning activity was held with the experiment class have a learning video as media. After the class took a posttest to find out the English skill enhancement which determine by using T-test. The result of t-test shows that experiment class obtained higher scores which can be concluded that video learning media is effective. After the posttest the researcher collected data through questionnaire which given to 30 students of experiment at the tenth-grade students at SMA Kristen Mercusuar Kupang, an Indonesian High School. After calculated the acquisition value of the questionnaire, the researcher obtained an average value of perception questionnaire (93) and also obtained the majority of each questionnaire item has a positive respond from the student. This shows that the using of English video learning media obtained a very good perception by the student in the classroom which directly proportional with higher posttest result achieved by experiment class. This finding can be considered as reference for the next studies about a relation between motivation, learning outcomes and the using of English Video learning Media